2020
DOI: 10.1111/bjd.19119
|View full text |Cite
|
Sign up to set email alerts
|

Intervention study to evaluate the importance of information given to patients with contact allergy: a randomized, investigator‐blinded clinical trial*

Abstract: Summary Background In contact dermatitis, it is crucial to understand and remember the outcome of patch testing. Unfortunately, many patients do not remember the results of their patch tests. Objectives Our aim was to evaluate the effects of an intervention programme in which extensive information on specific contact allergy was provided, in individuals with positive patch test reactions. Methods The study was designed as a randomized, investigator‐blinded clinical trial. Participants with positive test reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(34 citation statements)
references
References 25 publications
3
30
1
Order By: Relevance
“…5 Furthermore, recent prospective studies have demonstrated that patients often struggle to understand and recall the results of a patch test, especially those diagnosed with multiple allergens. 6,7 For many patients, navigating daily decisions about allergen avoidance can be difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Furthermore, recent prospective studies have demonstrated that patients often struggle to understand and recall the results of a patch test, especially those diagnosed with multiple allergens. 6,7 For many patients, navigating daily decisions about allergen avoidance can be difficult.…”
mentioning
confidence: 99%
“…One retrospective study on 1142 children found that over-the-counter products branded as “gentle skin care” still often provoke symptoms of dermatitis 5 . Furthermore, recent prospective studies have demonstrated that patients often struggle to understand and recall the results of a patch test, especially those diagnosed with multiple allergens 6,7 . For many patients, navigating daily decisions about allergen avoidance can be difficult.…”
mentioning
confidence: 99%
“…All patients were patch tested so as to meet the Swedish baseline series criteria of 2014 and the result was assessed as positive or negative. Of these, 46% (184 of 396) were diagnosed with one or more positive patch test reactions and were randomized into two groups, as previously described 14 . Patients with a negative patch test result were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…DLQI was measured by separate standard questionnaire on both occasions. Information on the patients' recollection of the contact allergy test results has previously been published 14 …”
Section: Methodsmentioning
confidence: 99%
“…In this issue of the BJD , Dizdarevic et al 1 report data from a questionnaire survey used to evaluate the effect of allergen awareness in patients undergoing patch testing. One group of patients was sent a reminder letter with additional test outcome information, in addition to the standard information.…”
mentioning
confidence: 99%